The performances of existing handicap facilities in rehabilitation building / Mohd Hafizudin Ahmad - Ahmad, Mohd Hafizudin (2009)
The level of handicap facilities in Malaysia nowadays is decreasing as there is no special organization to help monitor and upgrading the facilities for the disabled people. Disabled people themselves have complained and requested to the government by upgrading their facilities in order to provide pleasant workplace and ease their daily activities in the building. Handicap facilities such as ramp, wheelchair walkway, blind-track, handrail, elevator, handicap toilet and others relevant facilities for use by the disabled people are needed in all buildings in Malaysia especially in rehabilitation building.